Transcriptome analysis of the epididymis from Plag1 deficient mice suggests dysregulation of sperm maturation and extracellular matrix genes. Issue 12 (6th October 2020) - Wong, Joanne; Damdimopoulos, Anastasios; Damdimopoulou, Pauliina; Gasperoni, Jemma G.; Tran, Stephanie C.; Grommen, Sylvia V.H.; De Groef, Bert; Dworkin, Sebastian
Abstract: Background: The transcription factor pleomorphic adenoma gene 1 (PLAG1) is required for male fertility. Mice deficient in PLAG1 exhibit decreased sperm motility and abnormal epididymal tubule elongation and coiling, indicating impaired sperm maturation during epididymal transit. However, the downstream transcriptomic profile of the Plag1 knockout (KO; Plag1 −/− ) murine epididymis is currently unknown. Results: In this study, the PLAG1‐dependent epididymal transcriptome was characterised using RNA sequencing. Several genes important for the control of sperm maturation, motility, capacitation and the acrosome reaction were dysregulated in Plag1 −/− mice. Surprisingly, several cell proliferation genes were upregulated, and Ki67 analysis indicated that cell proliferation is aberrantly upregulated in the cauda epididymis stroma of Plag1 −/− mice. Gene ontology analysis showed an overall upregulation of genes encoding extracellular matrix components, and an overall downregulation of genes encoding metalloendopeptidases in the epididymides from Plag1 −/− mice. Conclusion: Together, these results suggest a defect in the epididymal extracellular matrix in Plag1 −/− mice. These results imply that in addition to maintaining epididymal integrity directly, PLAG1 may also regulate several genes involved in the regulation of sperm maturation and capacitation. Moreover, PLAG1 may also be involved in regulating tissue homeostasis and ensuring proper structure and maintenance of the extracellular matrix in the epididymis. Key Findings: A number of genes important for the control of sperm maturation, motility, capacitation and the acrosome reaction are dysregulated in Plag1 −/− mice. Cell proliferation is aberrantly upregulated in the cauda epididymis stroma of Plag1 −/− mice. Plag1 −/− mice present with substantial dysregulation in genes that regulate extracellular matrix components, suggesting a defect in the extracellular matrix.